Correlation Between Knowledge and Attitude Toward Treatment Adherence Among Patients with Type 2 Diabetes Mellitus in Makassar, Indonesia - Zulfiah Zulfiah; Yuniharce Kadang; Suprapto Suprapto (Direktorat Politeknik Kesehatan Makassar, 2025)
Many patients with diabetes mellitus still exhibit low adherence to long-term treatment. This study aimed to analyze the correlation between knowledge and attitude with treatment adherence among patients with type 2 diabetes mellitus. This research employed an analytical observational design with a cross-sectional approach. The study population consisted of patients receiving outpatient care at Nur Ichsan Clinic, Makassar City, from January to April 2025. A total of 74 respondents were selected using accidental sampling. Research instruments included the Diabetes Knowledge Questionnaire (DKQ-24), Diabetes Self-Management Education (DSME) attitude scale, and the Diabetes Self-Management Questionnaire (DSMQ) for treatment adherence. Each instrument had been validated in Indonesian with Cronbach’s alpha values of 0.82 (DKQ), 0.79 (DSME), and 0.85 (DSMQ), indicating good internal consistency. Knowledge, attitude, and compliance scores were categorized as good, fair, or poor based on mean cut-off points obtained from the total score distribution, as the data were normally distributed according to the Kolmogorov-Smirnov test (p = 0.119). Data were analyzed using Pearson’s correlation test, as the data met the assumptions of normality. The results showed that most patients had good levels of knowledge (75.7%), positive attitudes (75.7%), and high treatment adherence (75.7%). There was a significant positive correlation between knowledge and treatment adherence (r = 0.614, p < 0.001) and between attitude and treatment adherence (r = 0.587, p < 0.001). These findings indicate that patients with higher knowledge and more positive attitudes are more likely to adhere to treatment recommendations. In conclusion, knowledge and attitude are strongly correlated with treatment adherence among patients with type 2 diabetes mellitus. It is recommended that health education programs be strengthened through structured diabetes self-management interventions focusing on knowledge enhancement and attitude change to improve long-term adherence